On becoming virtuous: A life examined through the prism of Aristotle and Aquinas - Francis, Prudence Mary (Curtin University, 2013)
This thesis is an inquiry into the lived experience of becoming virtuous. Aristotle’s Nicomachean Ethics and St Thomas Aquinas’ Summa Theologica are the foundation texts used in this inquiry. These works reveal three significant elements concerning the essence of coming to virtue. These elements give rise to questions that have been applied to an interrogation of a life narrative that reveal understandings of the experience of becoming virtuous.